A Poética do corpo no mito e na dança butô: por uma educação sensível - Tibúrcio, Larissa Kelly de Oliveira Marques (2005)
The thesis presents the body poetry and its inscribing in the myth and Butô dance. The argumentation highlights the sensitive dimension present in these itineraries, as a possibility to operate the emergency of knowing inscribed in the body, bringing a kind of rationality that links the fragments, that allows the knowing to break through the barriers of disciplinary isolation, that abandons the certainties and goes through the ways of creation and that gives the body new space and time, featuring epistemological elements, ethical and esthetical, that can permit a sensitive education. All along the way, we comprehend by sensitive education, a education that considers the relinking of logical, analogical, symbolic and artistic knowledge and therefore reconsiders the own act of knowing as a continuous and inconcluded process. That sensitive education is also understood as retaking the body experience, its sensitive nature, as well as being meaningful to reading the world. It includes the body memory, its history and creativity, opening it to innovation, change, sense amplification and dialogue with other bodies and world, because it is within them. It is about an investigation of phenomenologic nature, that dialogues philosophy and art, pointing breakdowns of this reflection foe the body and education studies. We find it necessary to notice the body language, that allows one to think through movements, articulate a thought that is risen from articulations, guts and all the body. This incarnated reason starts the expressive body action, that makes us move to mean, communicate, inaugurate senses. Among these senses, we present a possibility of approach of the elements of Butô dance teaching and physical education, as ways of sensitive education showings of body poetry